2017
DOI: 10.1002/adma.201605148
|View full text |Cite
|
Sign up to set email alerts
|

Alkali‐Assisted Synthesis of Nitrogen Deficient Graphitic Carbon Nitride with Tunable Band Structures for Efficient Visible‐Light‐Driven Hydrogen Evolution

Abstract: A facile synthetic strategy for nitrogen-deficient graphitic carbon nitride (g-C N ) is established, involving a simple alkali-assisted thermal polymerization of urea, melamine, or thiourea. In situ introduced nitrogen vacancies significantly redshift the absorption edge of g-C N , with the defect concentration depending on the alkali to nitrogen precursor ratio. The g-C N products show superior visible-light photocatalytic performance compared to pristine g-C N .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
1,035
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,872 publications
(1,096 citation statements)
references
References 81 publications
56
1,035
1
4
Order By: Relevance
“…The copolymerization with barbituric acid was studied and realized the continuous band structure modification. Zhang et al [80] proposed the nitrogen defects introduced into g-C 3 N 4 with the addition of KOH during the calcination of urea, melamine, or thiourea. The band structure of the as-obtained g-C 3 N x was also been continueus tuned.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…The copolymerization with barbituric acid was studied and realized the continuous band structure modification. Zhang et al [80] proposed the nitrogen defects introduced into g-C 3 N 4 with the addition of KOH during the calcination of urea, melamine, or thiourea. The band structure of the as-obtained g-C 3 N x was also been continueus tuned.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…8c-h). 56 The results revealed that the bandgap energy of defective g-C 3 N x decreased from 2.67 to 2.17 eV after introducing defects, which was attributed to the altered C 2p and N 2p orbitals in the conductive band of defective g-C 3 N x as compared to those of the pristine g-C 3 N 4 . All these experimental and theoretical results demonstrated that the defects in carbonbased materials play a vital role in (photo)-electrocatalysis, which highlights the need to unveil their catalytic mechanism urgently.…”
Section: Materials Chemistry Frontiers Reviewmentioning
confidence: 80%
“…urea). 56 They found that the N defect density increased with the ascending amount of KOH addition, as evidenced by the appearance of cyano groups (-CRN) and the diminishing peak of N-H bond in the FTIR spectra (Fig. 8a).…”
Section: Materials Chemistry Frontiers Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, certain two-dimensional (2D) materials [17][18][19], particularly bismuth-based compounds, such as BiOX (where X is Cl, Br, or I) [20]Bi 2 O 3 [21], and BiVO 4 [22], have been widely used in photocatalysis and have attracted attention for their high photocatalytic performance in the treatment of organic pollutants and nitrogen fixation in water [23,24]. In particular, 2D BiOX nanomaterials have gained more interest in recent years.…”
Section: Introductionmentioning
confidence: 99%